2023
DOI: 10.3390/microorganisms11030542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Nanoparticles on Microbes

Abstract: Nanoparticles widely exist in nature and may be formed through inorganic or organic pathways, exhibiting unique physical and chemical properties different from those of bulk materials. However, little is known about the potential consequences of nanomaterials on microbes in natural environments. Herein, we investigated the interactions between microbes and nanoparticles by performing experiments on the inhibition effects of gold, ludox and laponite nanoparticles on Escherichia coli in liquid Luria–Bertani (LB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The differences in the antimicrobial activity of nanoparticles across different microbes are well-documented in the literature. Differences depend on the microbe and the activity of the nanoparticles, among other factors [ 97 , 98 ]. An interaction without significant differences is reflected in Table 3 with Ag-PPE_ SA and with Ag-BBE_ CA in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The differences in the antimicrobial activity of nanoparticles across different microbes are well-documented in the literature. Differences depend on the microbe and the activity of the nanoparticles, among other factors [ 97 , 98 ]. An interaction without significant differences is reflected in Table 3 with Ag-PPE_ SA and with Ag-BBE_ CA in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Assumingly, the chitosan moiety brings chitosan-silver nanocomposites close to bacteria, allowing intimate contact between the bacterial cell surface and antimicrobial materials – chitosan and silver – to enhance their antibacterial action. Moreover, it has been demonstrated that NPs may induce cell aggregation due to cell membrane disruption or through the induction of stress response and the production of extracellular polymeric substances (EPS), which leads to the assembly of cells [51].…”
Section: Resultsmentioning
confidence: 99%
“…214 and it has also been reported that microbial cells are able to detoxify NPs by coagulating NPs with extracellular polymeric substances or by changing nanoparticle morphologies. 215 Hence, the interactions between microorganisms and nanoparticles in the natural environment should receive more attention.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%